2010
DOI: 10.1016/j.bbrc.2010.01.123
|View full text |Cite
|
Sign up to set email alerts
|

Excess iodide decreases transcription of NIS and VEGF genes in rat FRTL-5 thyroid cells

Abstract: Although it is well known that an excess of iodide suppresses thyroid function and blood flow in vivo, the underlying molecular mechanisms are not fully known. The functional effect of iodide occurs at multiple steps, which include inhibition of sodium/iodide symporter (NIS) expression, transient block of organification, and inhibition of hormonal release. The vascular effect likely involves suppression of the vascular endothelial growth factor (VEGF) gene. In this report, we show that excess iodide coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…As previously reported, SLC5A5 expression was significantly suppressed by increasing concentrations of iodide (Fig. 5A) (27,31,39). The ability of iodide to decrease Slc5a5 expression was inhibited by perchlorate as seen in FRTL-5 cells (Supplementary Fig.…”
Section: Innate Immune Activation Of the Thyroid Is Induced By Iodidesupporting
confidence: 82%
“…As previously reported, SLC5A5 expression was significantly suppressed by increasing concentrations of iodide (Fig. 5A) (27,31,39). The ability of iodide to decrease Slc5a5 expression was inhibited by perchlorate as seen in FRTL-5 cells (Supplementary Fig.…”
Section: Innate Immune Activation Of the Thyroid Is Induced By Iodidesupporting
confidence: 82%
“…Our results support and extend these data by demonstrating that the decrease in NIS mRNA does not take place at the transcriptional level. This result is also in agreement with recent data showing I Ϫ effects on NIS mRNA stabilization (23) but is in contradiction to the findings of other authors who used higher I Ϫ doses (10 mM) (32). Furthermore, we found no regulation of Pax8 expression or its …”
Section: Discussionsupporting
confidence: 50%
“…Potassium perchlorate is a potent inhibitor of thyroidal iodide uptake [39] and we have shown it to similarly inhibit placental iodide uptake. While there is experimental evidence of low iodide intake resulting in increased NIS expression in an animal model [14], the authors are not aware of any published work implicating high iodide intake downregulating NIS as has been described in the thyroid [38]. Among the pregnancy-associated hormones studied, we have identified in particular hCG, oxytocin and prolactin as the most likely candidates in promoting uptake of iodide by the placenta.…”
Section: Discussionmentioning
confidence: 96%
“…While it is well established that in the thyroid NIS-mediated transport of iodide is driven by the electrochemical sodium gradient generated by the Na(+)/K(+)-ATPase [36], it remains unclear through which pathway 17β-estradiol may act to influence NIS expression [37]. It has been shown that in common with thyroid [38], enhancement of NIS expression and 125 I uptake by retinoids (RA) in lactating breast tissue can be diminished by 17β-estradiol treatment [39], which is in contrast to the positive findings demonstrated by Tazebay et al [20] and in this study, albeit in different tissues. Therefore, it remains unclear through which pathway estrogens may act to influence NIS expression.…”
Section: Discussionmentioning
confidence: 99%